Labour productivity and international competitiveness / Mohd. Yusof Kasim and Zulkifly Osman - Kasim, Mohd. Yusof; Osman, Zulkifly (1992)
Considering the openness of the Malaysian economy in which more than 50% of its Gross National Product are derived from exports and the rapid change of international demand pattern, enhancing its export competitiveness has become an important agenda in her industrial development strategy. For the 1990's, as trade in manufactured goods is fast expanding in significance and diversity and Malaysia is increasingly dependent on the export of these products, the critical elements for Malaysia's success in the global market are in maintaining and enhancing its competitive edge. In meeting the above objectives, it is essential for the State to provide a policy framework that will help our industry to adapt to changes in international competitiveness. There is also a need for the private sector to double its efforts in ensuring productivity growth, Research and Development activities, reduction in unit labour cost and capital investment. Against the above background, this paper will mainly examine the relative position of Malaysian labour productivity and its relationship with competitiveness vis-a-vis the Newly Industrialised Countries (NICs). The paper also attempts to discuss some major issues relating to efforts in enhancing labour productivity and competitiveness.